La responsabilità civile nel settore agroalimentare tra principio di precauzione e tutela della salute - Bonini, Roberta (Cultura giuridica e diritto vivente, 2019)
[Civil liability in the agri-food sector between the precautionary principle and health protection] As part of the legal and cultural evolution of food law, the Author examines the issue of civil liability in the agri-food sector through the necessary coordination of the Community legislation on food safety, based on the precautionary principle, as the supreme guarantor of the right to health, and that on the responsibility of the producer merged into the Consumer Code.